Environmental Law Enforcement In Indonesia In Terms Of The Concept Of Sustainable Development - Baren Sipayung; Indah Dwiprigitaningtias; Rahmat Joko Nugroho; Bartolomeus Bernard (Jurnal Hukum dan HAM Wara Sains, 2023)
The breadth of Indonesian life includes space, the location of a country The ongoing transparency of the Republic of Indonesia Archipelago sovereignty, sovereign rights and under jurisdiction. That means the government is obliged to manage life including regulatory policies, use, maintenance, renewal, supervision and control of Indonesia's environmental coverage. Factor: So, the government acts as a barrier to check the operation environmental management. Government is a mechanism that establishes the guidelines for the institution's design and long-term care. The formulation of the problem in this study is how to implement Indonesian environmental law in light of the idea of sustainable development. Descriptive research is what has been done. The kind of study used in this article includes doctrinal and normative legal research. In conclusion, enforcing environmental laws effectively is essential to fulfilling Indonesia's sustainable development objectives. It is necessary to improve and improve existing laws, better coordination between institutions, and increase public awareness about the importance of the environment. The government and society must work together to achieve this goal and ensure that Indonesia can achieve sustainable development.